An Integrated Molecular Approach to Predict Caffeine Analogs for Enhancing Cholinergic Signaling and Neuroprotection - Obiol, Diego Javier (2023)
In our study, we designed forty-one caffeine analogs with the aim of improving the modulation of acetylcholinesterase (AchE, PDBid: 4EY7) and activating the neuronal nicotinic acetylcholine receptor (α7-nAchR, PDBid: 7EKI) more effectively than the prototype caffeine. The central purpose of this work was to enhance cholinergic neurotransmission. Analogue T-44 emerged as the most promising due to its high affinity for both targets. However, we expanded our analysis to assess the impact of all designed analogs on two other molecular targets: the muscle nicotinic acetylcholine receptor (PDBid: 7QL5) and the human adenosine receptor (hA2AR, PDBid: 3RFM), a G protein- coupled receptor, class A. Inhibition of hA2AR by caffeine could also offer potential benefits in terms of neuroprotection. We conducted a thorough analysis of the pharmacokinetic and molecular properties of each analog and performed molecular docking at the orthosteric sites of the targets to determine the binding affinity score. For the prediction of pharmacokinetic parameters, we used pkCSM and SwissADME, and for performing molecular docking, we employed AutoDock Vina. We compared these results with known compounds to identify potential candidates with a high potential to modulate the activity of multiple target molecules simultaneously. Our findings reveal that some analogs, in addition to the prominent T-44, emerge as potential candidates to enhance cholinergic activity and potentially provide neuroprotection. In future studies, we plan to carry out molecular dynamics simulations and in vitro analyses to confirm the effects of these analogs on molecular targets. This work presents qualitative structure-activity relationship studies that provide relevant information for the design of new molecules that could enhance neurotransmission and neuroprotection.